Vitamin D supplementation alleviates insulin resistance in prediabetic rats by modifying IRS-1 and PPARγ/NF-κB expressions - Krisnamurti, Desak Gede Budi; Louisa, Melva; Poerwaningsih, Erni H.; Tarigan, Tri Juli Edi; Soetikno, Vivian; Wibowo, Heri; Nugroho, Christian Marco Hadi (Frontiers in Endocrinology, 2023)
Background Prediabetes is a condition of intermediate hyperglycemia that may progress to type 2 diabetes. Vitamin D deficiency has been frequently linked to insulin resistance and diabetes. The study aimed to investigate the role of D supplementation and its possible mechanism of action on insulin resistance in prediabetic rats. Method The study was conducted on 24 male Wistar rats that were randomly divided into 6 rats as healthy controls and 18 prediabetic rats. Prediabetic rats were induced with a high-fat and high-glucose diet (HFD-G) combined with a low dose of streptozotocin. Rats with the prediabetic condition were then randomized into three groups of 12-week treatment: one group that received no treatment, one that received vitamin D3 at 100 IU/kg BW, and one group that received vitamin D3 at 1000 IU/kg BW. The high-fat and high-glucose diets were continuously given throughout the twelve weeks of treatment. At the end of the supplementation period, glucose control parameters, inflammatory markers, and the expressions of IRS1, PPARγ, NF-κB, and IRS1 were measured. Results Vitamin D3 dose-dependently improves glucose control parameters, as shown by the reduction of fasting blood glucose (FBG), oral glucose tolerance test (OGTT), glycated albumin, insulin levels, and markers of insulin resistance (HOMA-IR). Upon histological analysis, vitamin D supplementation resulted in a reduction of the islet of Langerhans degeneration. Vitamin D also enhanced the ratio of IL-6/IL-10, reduced IRS1 phosphorylation at Ser307, increased expression of PPAR gamma, and reduced phosphorylation of NF-KB p65 at Ser536. Conclusion Vitamin D supplementation reduces insulin resistance in prediabetic rats. The reduction might be due to the effects of vitamin D on IRS, PPARγ, and NF-κB expression.